How do the Entrepreneurial Motivations and Struggles of Egyptian Women Entrepreneurs Challenge Existing Perspectives? - Sherif, Salma (AUC Knowledge Fountain, 2024)
This paper examines ten profiles of Egyptian women entrepreneurs and compares their perspectives to the widespread and main arguments in the existing literature reviewed on the topic; mainly their entrepreneurial motivation and challenges. The paper reveals similarities and contradictions, and introduces different angles to perceiving both aspects. The researcher concludes that contextualizing entrepreneurial motivations can, therefore, disclose deeper dimensions to the subject matter, and as for the challenges, it can change their relative importance. For the primary data collection, the paper follows a non-probability sampling approach by applying a purposive sampling technique. Semi-structured, in-depth interviews were conducted accordingly. The women entrepreneurs chosen varied in operating sector, age, marital status, and educational background. Yet, they all belonged to an affluent socio-economic class, which is utilized by the researcher for contextualization. The results showcase that the sample’s entrepreneurial motivations cover a variety of features, including social, economic, familial, and personal aspects, rather than primarily being necessity-driven. As for the challenges, the results illustrate that the sample perceives the primarily ones reported in the literature with less intensity and that they are generally satisfied with the sized and performance of their businesses. Furthermore, they highlight interlinkages between the entrepreneurial motivations and the challenges reported by the interviewees that have gone unseen in previous studies. The research concludes the need to approach the study of women entrepreneurship with gendered-lens. This entitles revisiting definitions, such as success. Moreover, the paper concludes that coupling the integration of context with the integration of gendered frameworks is essential in understanding the dynamics of women entrepreneurs in Egypt and in assessing their progress, and hence, in developing more relevant support mechanisms and interventions. The research on Egyptian women entrepreneurs is vital as this paper is a response to 1) the scarcity of existing research within the context of Egypt, 2) the lack of thorough interpretations of women entrepreneurial drivers and challenges, and 3) the absence of contextualization in existing studies on the entrepreneurial motivations of Egyptian women and their main challenges.